2016
DOI: 10.1038/srep32030
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of surgical brain injury by immune tolerance induced by intrathymic and hepatic portal vein injection of brain antigens

Abstract: Surgical brain injury (SBI) defines complications induced by intracranial surgery, such as cerebral edema and other secondary injuries. In our study, intrathymic and hepatic portal vein injection of allogeneic myelin basic protein (MBP) or autogeneic brain cell suspensions were administered to a standard SBI model. Serum pro-inflammatory IL-2, anti-inflammatory IL-4 concentrations and the CD4+T/CD8+T ratio were measured at 1, 3, 7, 14 and 21 d after surgery to verify the establishment of immune tolerance. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…In the animal model of TBI, the injection of self-CSF and self-brain-homogenate into the thymus can induce the immune tolerance of brain antigen, which has therapeutic effect. [ 12 108 109 ] We then confirmed that intrathymic injections of brain antigens can induce immune tolerance by the reeducation function of the thymus. [ 110 ] In that study, T cells were isolated from the spleens of C57BL/6 mice after intrathymic injection of MBP in the experimental group.…”
Section: T Hymus T Olerancementioning
confidence: 68%
See 3 more Smart Citations
“…In the animal model of TBI, the injection of self-CSF and self-brain-homogenate into the thymus can induce the immune tolerance of brain antigen, which has therapeutic effect. [ 12 108 109 ] We then confirmed that intrathymic injections of brain antigens can induce immune tolerance by the reeducation function of the thymus. [ 110 ] In that study, T cells were isolated from the spleens of C57BL/6 mice after intrathymic injection of MBP in the experimental group.…”
Section: T Hymus T Olerancementioning
confidence: 68%
“…[ 27 ] Inducing immune tolerance to MBP can reduce the occurrence of secondary inflammation and provide neuroprotection after brain injury. [ 28 29 ]…”
Section: Mmunological C Haracteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Aspects of B cell biology [ 31 ] and T cell interactions with respect to MS have been more extensively reviewed elsewhere [ 32 ]. Interestingly, in surgical brain injury, it has been found that immune tolerance can be induced by hepatic portal vein and intrathymic injection of MBP [ 33 ]. Possibly, in individuals who are not affected by MS, continuous exposure to low levels of modified MBP via the route depicted in Figure 4 may act in a similar manner to therapeutic administration of a causative antigen as outlined by Verhagen et al [ 34 ].…”
Section: Considerations If Ms Results From Age-related Changes Tomentioning
confidence: 99%